Human communication, the internet, medicine and its addictions - Gómez Almaguer, David; Acosta Olivo, Carlos Alberto; García Quintanilla, Emma Bertha; Jaime Pérez, José Carlos (UANL. Facultad de Medicina, 2015)
Communication amongst human beings is vital for the development and support of the human race. It is impressive how we have gone from smoke signals, carrier pigeons, ‘‘foot’’ or ‘‘horse’’ messengers, to land and air mail, fax, and telephones. However, nothing is as interesting and as incredible as communication through the internet and its derivations, like ‘‘social networks’’ and the use of the smartphone. This device allows the user to be connected with practically everybody, it even allows audio and video recording and to make commercial transactions. The question is, how does this impact health, science and medicine? The answer is not that simple, and we approach this topic in this issue of Medicina Universitaria